Boundaryless careers and algorithmic constraints in the gig economy. Issue 22 (16th December 2022) - Duggan, James; Sherman, Ultan; Carbery, Ronan; McDonnell, Anthony
Abstract: With low barriers to entry and ease of access to work, the gig economy offers the prospect of boundaryless opportunities for flexible working arrangements characterised by increased autonomy. This form of work, however, may leave individuals without development opportunities and could stymie career progression. Drawing on boundaryless career theory, this study examines the potential of gig workers to develop the transferable career competencies required to effectively pursue opportunities beyond these precarious roles. Through insights from 56 gig worker interviews, we analyse the lived experiences of workers in attempting to develop 'knowing-why', 'knowing-how', and 'knowing-whom' competencies. In so doing, we find that the potentially unmovable boundaries posed by algorithmic management practices within platform organisations constrains workers' abilities to navigate their roles and develop transferable competencies. The study lends empirical support to the bounded effect of gig work on individuals' careers in a domain characterised by precarity where organisations dismiss the existence of an employment relationship, where individuals may simultaneously work for multiple platforms, and where secretive algorithms heavily influence the experience of work.